Survey design and analysis using TURBOSTATS - Hart, Mike. (London ; New York : Chapman and Hall, 1993)
This book is about: The processes and perils of research; Using a questionnaire; The TURBOSTATS package; Frequency distributions; Analysis of continuous variables; ...
Keywords: Methodology; Computer programs; TURBOSTATS; TURBOSTATS; Surveys -- Methodology -- Computer programs; Social sciences -- Statistical methods -- Computer programs